Coronoid Foramina in a Pediatric Mandible: An Incidental Finding of a Morphologic and Developmental Anatomic Variant as a Distinctive Documented Feature - S Ghousia; C S Nyer Firdoose (Wolters Kluwer Medknow Publications, 2021)
The new advancing technologies have created a storm in the long-existing canons of anatomic sciences with the bandwagon of recent anatomical discoveries such as the existence and identification of a bilateral foramen in the coronoid process of the mandible. The coronoid process being a thin flat triangular process varies in shape and size and gives attachment to the main muscles of mastication the temporalis and the masseter. The excitement of exploratory anatomic victory on mysteries related to the anatomy of the head-and-neck region specific to the coronoid process was further documented and elaborated as an incidental finding. The following manuscript presents an intriguing case of a pediatric patient aged 7 years with a morphologic variation of coronoid process with presence of foramina bilaterally along with few other variants, further attempting to emphasize its occurrence in the developmental years as a possibility of developmental variant trait.